Approaches to enhance the investment attractiveness of multinational organizations - Andrey V Koren; Valentina A Vodopyanova (Revista de Investigaciones Universidad del Quindío, 2022)
Contemporary research on investment attraction procedures has tremendous significance. Generally, the actions of economic flow at the global rate are defined by the attractiveness of investment notion. A specific principle in absorbing and investments placement is allotted to multinational organizations, which hold the biggest effect on the global financial resources’ movement. The primary objective of the study is a deep investigation and assessment of approaches dedicated to raising investment and appealing to multinational organizations. The basic analysis laws for organizations in relation to the evaluation of their attractiveness of investment are taken into account. The study analyses the features of research of private and institutional investors with the biggest transnational organizations. The study also evaluates the arenas for investments as an element of investments’ appeal. Analysis of data shows a continuous fall in the relation between its indexes and the investment attractiveness of the 50 biggest organizations worldwide. It can be inferred that securities repurchase, industry examination, and diversifying organization activities may be deemed as the most efficient approach to raise the lasting attractiveness of investment in organizations.